2011
DOI: 10.1063/1.3653390
|View full text |Cite|
|
Sign up to set email alerts
|

Performance enhancement of blue light-emitting diodes with a special designed AlGaN/GaN superlattice electron-blocking layer

Abstract: The characteristics of the nitride-based blue light-emitting diode (LED) with an AlGaN/GaN superlattice (SL) electron-blocking layer (EBL) of gradual Al mole fraction are analyzed numerically and experimentally. The emission spectra, carrier concentrations in the quantum wells, energy band diagrams, electrostatic fields, and internal quantum efficiency are investigated. The results indicate that the LED with an AlGaN/GaN SL EBL of gradual Al mole fraction has a better hole injection efficiency, lower electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
68
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(68 citation statements)
references
References 9 publications
0
68
0
Order By: Relevance
“…The inclusion of additional layers with different polarisation constants and doping levels into the structure of the QW will also affect the strength of the total electric field across the QWs in the active region, leading to a further modification to the radiative recombination rates within the LED. It has been suggested that such an effect occurs when an EBL is included within a quantum well stack [13,14]. In this paper we investigate the effect that the inclusion of an EBL in the structure of an LED has on its conduction and valence band profiles and measured the resultant changes in the radiative recombination rate using low temperature PL decay measurements.…”
mentioning
confidence: 99%
“…The inclusion of additional layers with different polarisation constants and doping levels into the structure of the QW will also affect the strength of the total electric field across the QWs in the active region, leading to a further modification to the radiative recombination rates within the LED. It has been suggested that such an effect occurs when an EBL is included within a quantum well stack [13,14]. In this paper we investigate the effect that the inclusion of an EBL in the structure of an LED has on its conduction and valence band profiles and measured the resultant changes in the radiative recombination rate using low temperature PL decay measurements.…”
mentioning
confidence: 99%
“…6 To increase the ionization efficiency of the Mg dopants, a ptype GaN/AlGaN supperlattice was previously employed as the electron blocking layer. 7,8 Also, the Mg dopants were reported to be more efficiently ionized under polarizationinduced electric fields within the supperlattice, which is known as Poole-Frenkel effect. 9 Recently, it has been also reported that the hole concentration can be increased through the polarization doping.…”
mentioning
confidence: 99%
“…1,2 To this end, tremendous efforts have been devoted to improve the LED performance through addressing various issues related to material quality, structure optimization, and device design and fabrication. [3][4][5][6][7][8][9][10][11][12] Among these issues, to date a low p-type doping efficiency remains as a limiting factor, which adversely affects the LED performance. In typical p-type GaN, the resulting hole concentration is low because only $1% of Mg dopants are ionized at room temperature.…”
mentioning
confidence: 99%
“…[1][2][3] Consequently, tremendous efforts have been devoted to address these issues to improve the LED performance. As a result, structures such as engineered AlGaN electron-blocking layer (EBL), [3][4][5] p-type InGaN hole reservoir layer, 6 hole modulator by p-type doped last quantum barrier (QB), 7 AlGaN polarization doping, [8][9][10] and p-doped QBs, 11,12 etc., have been reported to enhance hole injection and reduce the efficiency droop. However, there is a lack of systematic investigations on how the p-type doping at different regions for the LED device influences the carrier transportation and hence the carrier recombination.…”
mentioning
confidence: 99%